2011
DOI: 10.1111/j.1365-2664.2011.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wind farms and food scarcity on a large scavenging bird species following an epidemic of bovine spongiform encephalopathy

Abstract: Summary 1.Wind farms are emerging as a major cause of mortality of large scavenging bird species, which may be catastrophic when they operate in concert with other threats. As a study model, we examine the impact of wind turbines on the population dynamics of a soaring bird species, when acting in conjunction with a sudden decrease in food availability following the European bovine spongiform encephalopathy (BSE) epidemic. 2. In Spain, vultures have been provided with supplementary food at traditional vulture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 46 publications
(55 reference statements)
1
72
1
Order By: Relevance
“…We present evidence of how these two consecutively occurring perturbations have been extremely effective in reducing the population density of a generalist opportunistic bird, which has not recovered in the three years following these events. Under strong perturbation pulses (Martı´nez-Abraı´n et al 2012) or intense environmental variability (Harding et al 2011), the density-dependent responses of demographic parameters appear insufficient to buffer population changes. Although an isolated perturbation, such as poisoning, seemed to have an important short-term effect, it is reasonable to believe that it was the closure of the landfill site that led to a permanent decrease in the carrying capacity of the system and hence a long-lasting reduction in population numbers, as previously suggested by Oro and Martı´nez-Abraı´n (2007).…”
Section: Implications For the Management Of Overabundant Speciesmentioning
confidence: 99%
“…We present evidence of how these two consecutively occurring perturbations have been extremely effective in reducing the population density of a generalist opportunistic bird, which has not recovered in the three years following these events. Under strong perturbation pulses (Martı´nez-Abraı´n et al 2012) or intense environmental variability (Harding et al 2011), the density-dependent responses of demographic parameters appear insufficient to buffer population changes. Although an isolated perturbation, such as poisoning, seemed to have an important short-term effect, it is reasonable to believe that it was the closure of the landfill site that led to a permanent decrease in the carrying capacity of the system and hence a long-lasting reduction in population numbers, as previously suggested by Oro and Martı´nez-Abraı´n (2007).…”
Section: Implications For the Management Of Overabundant Speciesmentioning
confidence: 99%
“…However, since the outbreak of the neurodegenerative disease in cattle, Bovine Spongiform Encephalopathy (BSE), mandatory regulations of the European Union led to the temporary closure of existing vulture restaurants in order to avoid the likely risk of transmission to humans (the Creutzfeldt-Jakob disease). Consequently, owing to this temporal food shortage, the populations of scavengers seem to have been affected, with survival and breeding success being reduced (CamiZa & Montelío 2006, Martínez-Abraín et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about ranging behaviour and spatial parameters. This is key to help managers to improve conservation measures aimed at combining the maintenance of scavengers' populations with sanitary legislation, as well as for the installation of wind-farms, which also constitute a potential source of mortality (Tellería 2009, Martínez-Abraín et al 2012. Traditional ringing schemes and radio-tracking studies have shown that the species ranges extensively, particularly juveniles (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of some diurnal migrating birds, such as raptors, makes them vulnerable to collisions with wind turbines, particularly if they are hunting (Higgins et al 2007, Garvin et al 2011, Martínez-Abraín et al 2012). Raptor mortality rates were particularly high at some early, large-scale wind energy facilities in California, e.g., Altamont (Orloff and Flannery 1992).…”
Section: Introductionmentioning
confidence: 99%